Profil PROFIL KEKERASAN PADA PEREMPUAN DAN ANAK PADA MASA PANDEMI COVID-19 DI PROVINSI NTB - Kisid, Kristin (EMBRIO, 2021)
The COVID-19 pandemic has an impact on the economic condition of the family which will directly contribute to the health condition of the family. The uncertain conditions during the COVID-19 pandemic could trigger violence, especially for women and children. The purpose of this study was to determine the profile of violence against women and children during the COVID-19 pandemic in NTB Province. This research is a type of quantitative research derived from secondary data. data on cases of violence against women and children were obtained from the results of reports from health centers, sub-districts, etc. that were collected in DP3AP2KB in 2020. Violence against women in NTB Province in 2020 increased by 26.05% from the previous year (2019). North Lombok Regency has the highest number of cases (140 cases) of violence against women that occurred during the COVID-19 pandemic in 2020. Violence that occurs in adult women is dominated by physical violence (61.18%) and violence that occurs in children dominated by violence in the form of sexual, namely 40.1%. The highest number of sexual violence against girls was in East Lombok Regency at 22.7%.